Development of a mobile application for prenatal care and content validation. - de Lima Costa Souza, Francisca Marta; Noleto dos Santos, Wenysson; da Costa Dantas, Janmilli; Alves de Sousa, Helena Rangel; Alencar Moreira, Olga Alice; Rosendo da Silva, Richardson Augusto (Acta Paulista de Enfermagem, 2022)
Objective: To develop a mobile application for pregnant women in prenatal care and validate its content. Methods: This is a methodological and technological study with a quantitative approach, carried out in three stages: integrative literature review, content validation, and application construction. The review was carried out in bibliographic databases; then, a guide instrument was elaborated covering subjects about prenatal care, childbirth and the puerperium, which underwent an initial validation through a focus group. For the application construction, the following phases were followed: analysis, design, development, implementation and expert assessment. The application construction and content validation were carried out by 21 experts, being 14 obstetric nurses and 7 Information and Communication Technology professionals. Content Validity Index (CVI) was used, considering as an agreement rate values above 80%, inter-rater agreement and Mann-Whitney non-parametric test to verify Delphi 1 and 2 phases. Results: The application has 111 screens about prenatal care, childbirth, puerperium and breastfeeding, the pregnant woman's virtual notebook, an alarm clock as a reminder of appointments and the contact us menu. After two rounds Delphi technique rounds, agreement was reached between the experts, with an average Content Validity Index of 0.89. Conclusion: The application obtained an adequate general CVI among experts, showing that the information covered and the system's technical part are reliable, being validated in terms of content. This presents itself as a potential instrument for health promotion with regard to care in the pregnancy-puerperal period.